1996
DOI: 10.1046/j.1468-2982.1996.1603183.x
|View full text |Cite
|
Sign up to set email alerts
|

A Quality of Life Instrument for Adolescents with Chronic Headache

Abstract: We developed a generic Quality of Life (QL) measurement scale for adolescents between 12 and 18 years of age, primarily for use on youngsters with chronic headaches or migraine. The Quality of Life Headache in Youth (QLH-Y) is a 71 item (69 multiple choice items and two visual analogue scales) QL measurement scale. It assesses an individual's QL in six QL subdomains. Study 1 (n = 223) was aimed at item selection and scale construction. Thirteen subscales were developed to cover the four QL subdomains Psycholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
84
1
12

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(100 citation statements)
references
References 18 publications
3
84
1
12
Order By: Relevance
“…For example, Langeveld et al (1996) found that adolescents suffering with headache and migraine reported lower overall HRQOL, including: decreased psychological functioning, increased physical symptoms, lower LS, and less general health (Langeveld et al 1996). Moreover, changes in headache and migraine activity in adolescents has been shown to be related to parallel changes in the HRQOL sub-domains of LS, health, and psychological functioning (see Langeveld et al 1997).…”
Section: Physical Healthmentioning
confidence: 99%
“…For example, Langeveld et al (1996) found that adolescents suffering with headache and migraine reported lower overall HRQOL, including: decreased psychological functioning, increased physical symptoms, lower LS, and less general health (Langeveld et al 1996). Moreover, changes in headache and migraine activity in adolescents has been shown to be related to parallel changes in the HRQOL sub-domains of LS, health, and psychological functioning (see Langeveld et al 1997).…”
Section: Physical Healthmentioning
confidence: 99%
“…8 Pediatric HRQOL measurement instruments must be sensitive to cognitive development and integrate both child self-report and parent proxy-report to reflect their potentially unique perspectives. Imperfect concordance between self-and proxy-report, termed cross-informant variance, 9 has been consistently documented among child/adolescent, parent, teacher, and healthcare professionals, reports in the HRQOL assessment of healthy children 10 and children with chronic health conditions, [11][12][13][14] including cancer. 15 Agreement has been demonstrated to be lower for internalizing problems (e.g., depression and pain) than for externalizing problems (e.g., hyperactivity and walking).…”
mentioning
confidence: 99%
“…This shows that parents or carers cannot replace the voice of a child. Besides, there have been significant concerns about the accuracy and acceptability of parent-proxy ratings of paediatric patients ' HRQOL tool [26,47,48].…”
Section: Sf-36mentioning
confidence: 99%
“…This shows that parents or carers cannot replace the voice of a child. Besides, there have been significant concerns about the accuracy and acceptability of parent-proxy ratings of paediatric patients ' HRQOL tool [26,47,48].The utility of a generic HRQOL tool for children or adolescents has not been explicitly tested in patients with neurodevelopmental disorders [25,26,39,[49][50][51][52][53]. There are very few paediatric neurosurgical clinical studies that use the HRQOL tools mentioned above to look into the clinical outcome of the patients [12][13][14][15]21,25,54].…”
mentioning
confidence: 99%